Research on the Structure of Peanut Allergen Protein Ara h1 Based on Aquaphotomics - Zhang, Mengqi; Liu, Liang; Yang, Cui; Sun, Zhongyu; Xu, Xiuhua; Li, Lian; Zang, Hengchang (Frontiers in Nutrition, 2021)
Peanut allergy is becoming a life-threatening disease which could induce severe allergic reactions in modern society especially for children. The most promising method applied for deallergization is heating pretreatment. However, the mechanism from the view of spectroscopy has not been illustrated. In this study, near infrared spectroscopy combined with aquaphotomics was introduced to help us understand the detailed structural changes information during the heating process. Near infrared spectra of Ara h1 were acquired from 25 to 80 oC first. Then, aquaphotomics processing tools including principal component analysis, continuous wavelet transform and two-dimensional correlation spectroscopy were utilized for better understanding the thermodynamic changes, secondary structure and the hydrogen bond network of Ara h1. The results indicated that about 55 oC could be a key temperature which was the structure change point. During the heating process, the hydrogen bond network was destroyed, free water was increased, and the content of protein secondary structure was changed. Moreover, it could reveal the interaction between the water structure and Ara h1 from the perspective of water molecules, and explain the effect of temperature on the Ara h1 structure and hydrogen bonding system. Thus, this study described a new way to explore the thermodynamic properties of Ara h1 from the perspective of spectroscopy, and laid a theoretical foundation for the application of temperature-desensitized protein products.